Electroweak symmetric dark matter balls - Ponton, Eduardo [UNESP] (2019)
In the simple Higgs-portal dark matter model with a conserved dark matter number, we show that there exists a non-topological soliton state of dark matter. This state has smaller energy per dark matter number than a free particle state and has its interior in the electroweak symmetric vacuum. It could be produced in the early universe from first-order electroweak phase transition and contribute most of dark matter. This electroweak symmetric dark matter ball is a novel macroscopic dark matter candidate with an energy density of the electroweak scale and a mass of 1 gram or above. Because of its electroweak-symmetric interior, the dark matter ball has a large geometric scattering cross section off a nucleon or a nucleus. Dark matter and neutrino experiments with a large-size detector like Xenon1T, BOREXINO and JUNO have great potential to discover electroweak symmetric dark matter balls. We also discuss the formation of bound states of a dark matter ball and ordinary matter.